2013
DOI: 10.1002/glia.22554
|View full text |Cite|
|
Sign up to set email alerts
|

Extensive regenerative plasticity among adult NG2-glia populations is exclusively based on self-renewal

Abstract: NG2-glia are known to proliferate in the adult brain, however the extent of their mitotic and regenerative capacity and particularly their adult origin is uncertain. By employing a paradigm of mitotic blockade in conjunction with genetic fate tracing we demonstrate that intracerebroventricular mitotic blocker infusion leads to wide-spread and complete ablation of NG2-glial cells in the hypothalamus and other periventricular brain regions. However, despite the extensive glia loss, parenchymal NG2-glia coverage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 54 publications
7
46
1
Order By: Relevance
“…In postnatal CNS, oligodendrogliogenesis is a continuous process that requires the self-renewal activity of progenitors, namely, OPCs, in the form of active mitosis (17,18). However, in our analyses, most NG2 + cells in the dorsal CTX did not give rise to OLs, and thus did not qualify as classical OPCs.…”
Section: Ng2 Lineage Development Shows Different Patterns In Early Pocontrasting
confidence: 59%
“…In postnatal CNS, oligodendrogliogenesis is a continuous process that requires the self-renewal activity of progenitors, namely, OPCs, in the form of active mitosis (17,18). However, in our analyses, most NG2 + cells in the dorsal CTX did not give rise to OLs, and thus did not qualify as classical OPCs.…”
Section: Ng2 Lineage Development Shows Different Patterns In Early Pocontrasting
confidence: 59%
“…This remains true for most of the CNS cell types, but some studies challenged this view by showing that many types of glial cells are able to self-maintain locally. Not only can oligodendrocyte progenitors establish their own homeostatic proliferation after depletion [67,68], but microglia can be stimulated to proliferate after pharmacological [10] or genetic [11] ablation. Both studies showed with immunohistological methods that the repopulating cells were BrdU + and Ki67 + .…”
Section: Conditional Genetic Deletion Modelsmentioning
confidence: 99%
“…They appear to sustain equidistance to one another through contact inhibition of their processes [10, 31]. When periventricular NG2-glia cells are ablated pharmacologically by exposure to the mitotic inhibitor cytosine-β-D-arabino­furanoside (AraC; see Box 1 for details on AraC-induced NG2-glia ablation), mice display a dramatic change in daily food intake, consuming up to twice as much chow as controls [32].…”
Section: Ng2-glia and Energy Balancementioning
confidence: 99%
“…The principle confirmed function of NG2-glia is to act as a lifetime source of new oligodendrocytes, and it is well established that NG2-glia continue to proliferate throughout adulthood in both white and grey matter [8], including in the hypothalamus [10, 11]. In fact, NG2-glia are the most proliferative cells in the adult brain [12].…”
Section: Introduction To Ng2-gliamentioning
confidence: 99%
See 1 more Smart Citation